PREMATURITY AND LOW BIRTH WEIGHT PARTICIPATION IN NEONATAL DEATHS AT GYNECOLOGY AND OBSTETRICS CLINIC IN SKOPJE IN THE PERIOD OF SEVEN YEARS - Ivanova, Gabriela Bushinoska; Bushinovska, Jasna; Ivanov, Jordancho (Journal of Morphological Sciences, 2020)
Most of the neonatal deaths at NICU, in the neonatal period of life 0-28 days after delivery are results of preterm births and complications from prematurity. Preterm birth is a birth before 37 g.w. of pregnancy. Neonatal mortality is a death among live- born new-borns in the first four weeks of life after delivery. Prematurity and low birth weight significantly participate in neonatal deaths at NICU. The purpose of the study is to show the participation of prematurity and low birth weight in neonatal mortality, between new-borns admitted and treated at NICU at the GOC-Skopje, in the period of seven years. The retrospective analysis showed the participation of prematurity and low birth weight in neonatal mortality at NICU, at GOC- Skopje in the period of seven years- 2011-2017. The data was collected from the Data basis of NICU and medical histories of new-borns at NICU, during this period. In the period of seven years there were 36706 live-born new-borns at GOC-Skopje. 4810 of them or 13.18% were admitted and treated at NICU. Neonatal mortality at NICU in the seven years period was 912 new-borns, or 19% from all neonates admitted at NICU. Most of them 867, or 95% of neonatal deaths were preterm births or new-borns delivered before 37 g.w. of pregnancy. The leading causes for neonatal death in new-borns treated at NICU were complications due to prematurity and low birth weight in new-borns, in the period of seven years 2011-2017. Prematurity and low birth weight participate in the most of neonatal deaths at NICU and should be prevented in the future. Key words : low birth weight, prematurity, preterm birth, neonatal mortality, GOC-Skopje, NICU